Progression from tuberculosis to multi drug resistance-TB in revised national tuberculosis control programme: perspectives from health system care givers - Kumar, Ashutosh; Rana, Rishabh Kumar; Sundram, Shalini; Sinha, Sudipta Kumar; Jaiswal, Richa; Kashyap, Vivek (International Journal Of Community Medicine And Public Health, 2019)
Background: The aims and objectives were to study the progression from tuberculosis to multi drug resistance-TB in revised national tuberculosis control programme: perspectives from health system care givers. Methods: The study was carried out in TB Sanatorium ITKI, Sadar Hospital Ranchi and RIMS Ranchi. The interview of various health personnel including SAHIYAs was taken using a semi-structured questionnaire based on programmatic management of multi drug resistant tuberculosis guidelines -2016. Results: Among Doctors knowledge level was good compared to other health personnel which had mean value 7.33 (±2.79), laboratory technician 3.45 (±2.64), STS 4.67 (±1.59), Sahiya 2.1 (±0.73). Regarding capacity enhancement level all health personnel needed refresher trainings in which doctors got 4.67 (±1.58), laboratory technician 3.45±2.64, STS 1.72±0.34, and Sahiya 0.5±0.52. Specially sahiya needs training regarding MDR-TB because they are the connecting link between health system and community. Regarding execution level, Doctors got 1.86 (±0.74), laboratory technician 1.64 (±0.56), STS 1.64 (±0.56) and Sahiya (ASHA) 2.2 (±0.44). Sahiya were better than other health personnel at execution level. Conclusions: Advocacy, communication, and social mobilization are important aspects of TB control, Policy makers and administrators should be sensitized for need of adequate and sustained funding for TB control to ensure quality capacity building. They need to provide continuous and quality training of staff at different levels and retention of trained staff and periodic reviews to identify gaps and take corrective steps.